Discretionary disclosure in the presence of dual distribution channels - Arya, Anil; Mittendorf, Brian (Journal of Accounting and Economics, 2013)
A prevailing view in the disclosure literature is that firms who learn favorable market information are reluctant to disclose it, fearing it will attract new rivals. In this paper, we demonstrate that the presence of dual distribution arrangements, wherein consumers can purchase products either from traditional retail firms or directly from suppliers, can notably alter disclosure incentives. As under prevailing views, a retailer disclosing positive news risks entry by competitors. However, entry shifts the incumbent supplier–retailer relationship: the presence of new competitors leads the supplier to treat its retailer more as a strategic partner, translating into lower wholesale prices. This, in turn, can lead the retailer to willingly share favorable news, since such disclosure invites entry precisely when the retailer stands to benefit most from price concessions. Our results suggest that as dual distribution continues to increase in prominence, firms may be more willing to voluntarily disclose sensitive financial information particularly that which points to high demand for its products.